Barriers and facilitators to the implementation of a midwifery-led-care model: a qualitative systematic review protocol - Soares Goncalves, Andreia (2023)
Introduction: Midwifery models of care are sustainable, cost-effective, safe, and effective models of care that have long been regarded as adequate and recommended for the care of women with uncomplicated pregnancies. The implementation of such models has, however, been very slow in countries where a medicalized culture towards pregnancy and birth prevails. Since there is no systematized evidence that examines the barriers and facilitators to the implementation of midwifery models of care. Objective: Identify and synthesize the literature on barriers and facilitators perceived by stakeholders to the implementation of a midwifery-led-care model in a healthcare system. Methods: The review will consider qualitative, and mixed methods studies. For the mix-methods studies only the qualitative component will be included in the review. No date limits will be applied. Studies written in English, Spanish and Portuguese will be included. The databases to be searched will include CINAHL (EBSCOhost), MEDLINE (EBSCOhost), PsycINFO (EBSCOhost), and Web of Science (EBSCO). Sources of grey literature include ProQuest Dissertations and Theses, and relevant organizational websites. Study selection, critical appraisal, data extraction, and data synthesis will be performed independently by 2 reviewers. The synthesized findings will be graded according to the ConQual approach for establishing confidence in findings. Discussion: We anticipate that our systematic review will provide guidance for the implementation of midwifery-led care models in any healthcare setting. Conclusion: This protocol sets out the planning and documents the methodology the researchers will employ in this systematic review.